Beta thalassemia in Turkey: |distribution, diversity, evolution and phenotype-genotype correlations - Tadmouri, Ghazi Omar. (Thesis (Ph.D.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
The present study illustrates the results of years of research on different aspects of beta-thalassemia in Turkey. Methods to detect the C-T change at position -158 upstream of the Gy-globin gene and the (AT)xTy motif 5' to the beta-globin gene were established and implemented. Analysis of these polymorphisms explained the reason behind the increased levels of fetal hemoglobin in nine out of 31 beta-thalassemia patients analyzed and demonstrated a dominant effect exerted by the XmnI Gy-globin polymorphism. Molecular screening of beta-globin genes in 19 beta-thalassemia individuals by genomic DNA sequencing uncovered the presence of 14 mutations; three of these are seen for the first time in Turkey. Another achievement made during this study is the compilation of beta-globin gene data collected since 1988 in a single repository. This allowed an easy mean to investigate the distribution of beta-globin gene mutations in various regions and towns of Turkey. This also demonstrated that the distribution of beta-thalassemia mutant alleles differed within each geographical area with a decreased gradient of mutation numbers from the East to the West of Anatolia. Analysis of nine polymorphic nucleotides and the (AT)xTy motif 5' to the beta-globin gene in 204 non-related beta-globin genes from Turkey exhibited 12 sequence haplotypes. Samples from the Black Sea region demonstrated a remarkable level of genetic heterogeneity in contrast to the homogeneity in Central Anatolian samples. Of the 22 beta-globin mutations analyzed, 18 were related with single sequence haplotypes and each of the other four were associated with a minimum of two sequence haplotypes. Our results demonstrate that the heterozygote advantage against malaria in Anatolia may have occurred at 6500-2000 BC by the oldest beta-thalassemia allele (i.e.,IVS-I-110 G-A). From that date on, most of the common beta-thalassemia mutations in Turkey were established and by the 13th century AD most of them were brought to frequencies close to what is observed at present.
Keywords: Thalassemia -- Turkey.; Genetic disorders.